PERENCANAAN PLTS ON-GRID BERDASARKAN PROFIL KONSUMSI ENERGI BERBASIS PVSYST PADA RUMAH KOS SEMBILAN KAMAR DI KOTA MALANG - Kurniawan, Ferryo Lenz; Wibawa, Unggul; Wijono, n/a (Jurnal Mahasiswa TEUB, 2024)
The adoption of solar power plants (SPP) has shown an increasing trend in recent years. However, earlier this year, the exportimport mechanism, which had been an attraction for solar power plants installation, was abolished through the Minister of Energy and Mineral Resources Regulation No. 2 of 2024. This means that any excess electricity production generated will no longer be counted as a deduction from electricity bills. With this regulatory change, the sizing of the designed solar power plants capacity needs to be adjusted to avoid excess energy production. Previously, the determination of installed solar power plant capacity was based on the available area or the maximum capacity of the installed customer class. However, now, the determination of installed SPP capacity must be based on electricity consumption during the solar radiation period, where in Malang City, solar radiation intensity is recorded from 6:00 AM to 5:00 PM WIB. The research method involves designing a solar power plant based on the site conditions and electricity needs. The research object is a boarding house located in Lowokwaru, Malang, with nine rooms. There are three potential locations for module installation: a flat roof facing northwest, a sloped roof facing southwest, and a sloped roof facing northeast. One location will be selected based on the highest solar radiation exposure with minimal shading to maximize electricity production. Shading simulation will be conducted using PVsyst 7.4 software. Additionally, the electrical installation for each room will be determined based on load profile derived from the load usage characteristic of each room. Based on simulations and calculations, it was determined that 5 Longi Solar LR5-66HPH-500M G2 500 Wp solar modules and 5 TSUN MS400 Microinverters with a DC/AC ratio of 1.25 will provide a performance ratio of 81.97%, supplying an average of 4,162 kWh annually. The initial capital expenditure for this solar power plant installation is IDR 43,738,989, with a return rate of 13.43% and a break even point achieved after 7 years and 11 months. Based on the feasibility study, the installation of this SPP system is deemed viable and profitable. Keywords— On-grid solar power plant, shading, load profile, economics.